Exploring the cross-linguistic functioning of the Principles of WH-Movements: The case of Pakistani ESL learners - Sidra Haroon; Muhammad Aslam; Tahir Saleem (Cogent Arts & Humanities, 2023)
This is a cross-linguistic study conducted with Pakistani learners of English in the classroom setting. This study aimed to explore whether the UG Principles of WH-movement supported or restricted Urdu-speaking learners in forming direct WH-questions in English. For data collection, a sample of 260 students was selected using convenience sampling from ten (10) private and four (04) public sector secondary schools from Lahore. To address the research questions of this study, frequency data were collected through Grammaticality judgment Tasks with thirty-six (36) WH-questions in Urdu. Each Urdu sentence is followed by two English translations (T1 & T2). The statistical analysis showed that UG Principles of WH-movement were fully available to Pakistani ESL learners whose L1 was Urdu. The study has important implications for the UG researchers in that more cross-linguistic studies are needed to verify Chomsky’s Hypothesized UG regarding non-English languages. The study also suggests revisiting the Critical Period Hypothesis. Besides, the teachers and materials developers of English grammar in non-native settings like Pakistan should rethink the role of direct instruction of rules and carrier content in teaching WH-questions to learners of English as a second language.